Electrodeless photo-assisted electrochemical etching of GaN using a H3PO4-based solution containing S2O82– ions. (31st May 2019) - Toguchi, Masachika; Miwa, Kazuki; Horikiri, Fumimasa; Fukuhara, Noboru; Narita, Yoshinobu; Yoshida, Takehiro; Sato, Taketomo
Abstract: Electrodeless photo-assisted electrochemical etching was successfully demonstrated using a H3 PO4 -based solution containing S2 O8 2– ions. The pH value of the solution changed under UVC illumination, clearly showing that SO4 ·– radicals were produced from S2 O8 2– ions by absorbing UVC light. The production rate of SO4 ·– radicals maintained a constant value over the wide pH range of the solution, leading to etching rates and surface roughness comparable to those obtained in KOH-based solutions. The positive-type photoresist was applicable as the etching mask for the H3 PO4 -based solution. This finding will contribute to the development of a simple wet etching process suitable for the manufacturing of GaN-based devices.